(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Necrotizing pancreatitis is a severe, death-threatening clinical form of acute pancreatitis. The current concept of treatment for necrotizing pancreatitis has changed. Treatment of necrotizing pancreatitis with percutaneous drainage intervention is gradually being applied at large centers. Objective: This study describes the clinical and paraclinical characteristics of necrotizing pancreatitis treated with percutaneous drainage. Subjects and methods: Retrospective descriptive study of cases diagnosed with necrotizing pancreatitis that were treated with percutaneous drainage at Binh Dan Hospital from October 2019 to September 2022. Results: There were 36 cases of necrotizing pancreatitis treated with percutaneous drainage that met the sampling criteria with the following characteristics: 26 male patients (72.22%) and 10 female patients (27.78%); On average, 46.31 ± 14.01 years old, the group under 50 years old accounts for the majority (63.87%), with a history of pancreatitis accounting for the highest proportion (44.4%). The main reason for hospitalization is abdominal pain, accounting for 58.33%. Symptoms include vomiting and fever, accounting for 58.33%. There were 3 patients with severe symptoms, accounting for 8.33%. The rate of organ failure when hospitalized in the first 48 hours is high, accounting for 39%. The average blood amylase was 528.89 ± 528.87 U/L. Balthazar score: Grade E accounts for 93.75%, Grade D accounts for 6.25%. Conclusion: Most cases of necrotizing pancreatitis treated with percutaneous drainage are more common in men than in women. MSCT scan is a necessary tool to diagnose necrotizing pancreatitis and plays an important role in indicating percutaneous drainage intervention.